Issues of Digital Trade Rules and Implications for Korea in the Post COVID-19 World. Issue 3 (30th September 2020) - Cho, Jungran; Ahn, Byunghee; Hong, Kyoungseo; Cheong, Inkyo
Abstract : As a countermeasure to the COVID-19 pandemic, countries are implementing social distancing and mask-wearing. In this situation, the use of digital devices and untact activities are increasing. As a result, domestic and international e-commerce is increasing, and data is growing rapidly. Developed countries with advanced artificial intelligence and big data technologies have been striving to establish international regulations for digital trade in order to create a business environment that is advantageous for their own companies. This paper examines the e-commerce trend since the outbreak of COVID-19 and analyzes major issues related to digital trade rules under discussion. In particular, this paper pointed out that although Korea is recognized to be an advanced country considering its stage of industrial development and income level, the nation maintains the position of developing countries regarding digital trade. Based on this, this paper attempted to draw implications for the development of Korea's digital trade in the post COVID-19 world.